2016
DOI: 10.1002/jpln.201600104
|View full text |Cite
|
Sign up to set email alerts
|

Can liming reduce barium uptake by agricultural plants grown on sandy soil?

Abstract: Uptake of barium (Ba) from soil by vascular plants varies among species. Despite the toxicity of soluble Ba compounds to plants, research on mechanisms controlling Ba uptake from natural soils is scarce. This study investigated the treatment effect of lime (CaCO3) added to a sandy soil containing a total of 500 mg Ba kg−1 on uptake and interspecies distribution of Ba in legumes and other cultivated food and feed plants. Nine species of grasses, vegetables, herbs, and legumes were cultivated under controlled co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
(38 reference statements)
3
12
0
3
Order By: Relevance
“…The content of Ba in plant tissues depends on numerous factors, including the plant species and the concentration of Ba in the soil, as well as the physicochemical properties of Ba and the condition of the soil, e.g., its humidity or aeration. The dependency of Ba accumulation on plant species is confirmed by the results obtained by Myrvang et al (2016). They demonstrated that legumes exhibit a higher accumulation of Ba from soil than grasses, vegetables or herbs.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…The content of Ba in plant tissues depends on numerous factors, including the plant species and the concentration of Ba in the soil, as well as the physicochemical properties of Ba and the condition of the soil, e.g., its humidity or aeration. The dependency of Ba accumulation on plant species is confirmed by the results obtained by Myrvang et al (2016). They demonstrated that legumes exhibit a higher accumulation of Ba from soil than grasses, vegetables or herbs.…”
Section: Methodssupporting
confidence: 56%
“…The study also found significant Ba removal capabilities in silvergrass Miscanthus floridulus. Barium accumulation was also observed in the biomass of southern cattail (Typha domingensis), papyrus sedge (Cyperus papyrus) (Ribeiro et al, 2018), Indigofera cordifolia (Raghu, 2001), Brazil nuts (Bertholletia excels), different mushrooms (Harbison et al, 2015) and some legumes (Myrvang et al, 2016). The latter observed that bird velch (Vicia cracca L.) and white clover (Trifolium repens L.) examined in a pot experiment carried out on sandy soil accumulated a higher amount of Ba than barley, tall fescue, carrot, radish and spinach.…”
Section: Introductionmentioning
confidence: 95%
“…). Myrvang et al () also demonstrated Ba uptake from this particular sand to tall fescue and white clover in a previous work. Despite that the sand contained nearly 20 times more Ba than carbonatite, an additional contribution to plant Ba from carbonatite was still evident, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…) and the close relationship between these two elements (Fig. ) agrees well with findings reported by Myrvang et al (). They reported that white clover accumulated these elements more effectively than tall fescue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation